Preoperative Bilirubin-Adjusted Carbohydrate Antigen 19-9 as a Prognostic Factor for Extrahepatic Cholangiocarcinoma Patients at a Single Center - Li, Jiayi (Cancer Manag Res, 2020)
PURPOSE: The aims of our study were to investigate the prognostic impact of the rate of preoperative serum carbohydrate antigen 19-9/bilirubin (CA19-9/BR) on patients with extrahepatic bile duct cancer. PATIENTS AND METHODS: We collected clinical data from 89 patients who underwent surgery for extrahepatic cholangiocarcinoma (ECC) at Peking Union Medical College Hospital between January 2012 and December 2017. The Kaplan–Meier analysis for univariate analysis and the Cox proportional hazards models for multivariate analysis were used to determine possible independent prognostic factors. RESULTS: CA19-9/BR was classified as elevated compared with normal based on the upper serum normal values of CA19-9 (37 U/mL) and bilirubin (1.5 mg/dL), which gives a cut-off at 25 U/mL/mg/dL. Univariate analysis showed that the overall survival of patients with a high CA19-9/BR ratio was significantly worse compared with patients with a low CA19-9/BR ratio (Hazard Ratio [HR] 2.149; 95% Confidence Interval [95% CI] 1.027–4.495; P=0.042). Multivariate analysis revealed that a high CA19-9/BR ratio (HR 3.250; 95% CI 1.165–9.067; P=0.024), low differentiation (HR 3.551; 95% CI 1.231–10.244; P=0.019), and positive margin (HR 2.555; 95% CI 1.111–5.875; P=0.027) remained independent prognostic factors after adjusting for age at diagnosis, maximal diameters, and other possible factors. CONCLUSION: The preoperative CA19-9/BR ratio is a good prognostic factor in predicting survival in ECC patients and closer follow-up is recommended in patients with a higher CA19-9/BR ratio before surgery.